Considerations for Managing Greenhouse Pests - Florida Greenhouse Vegetable Production Handbook, Vol 3 - J. R. Rich; S. E. Webb; M. L. Paret; M. T. Momol (EDIS)
This document is HS924, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date December 1990. Revised September 2013.